Biological Analysis of Blue Swimmer Crab (Portunus pelagicus) from Collectors in Lamongan, Tuban, Pasuruan, and Rembang, Java, Indonesia - Murni, Lini; Arfiati, Diana; Kurniawan, Andi; Kilawati, Yuni; Subarijanti, Herwati Umi; Suliswanto, Suliswanto; Syams, Muhammad Nafar Amani; Gumelar, Agum Bayu; Huda, Alif Raditya Amirul (The Journal of Experimental Life Science, 2018)
Blue swimmer crab (Portunus pelagicus) can increase the country's incomes due to its high demand of export. This study aims to determine biological analysis on the population of blue swimmer crab in Lamongan, Tuban, Pasuruan, and Rembang. The sampling location was based on the fishing area and the method used survey method from collectors in each location. The blue swimmer crab's biological characteristics which observed are the correlation on wide of carapace and blue swimmer crab weight, sex ratio, and gonad maturity level. The results showed the correlation between the wide and weight of carapace in Lamongan (male: 113.80-122.99 mm and 87.98-121.60 g then female: 108.21-117.27 mm and 71.80-99.74 g), Tuban (male: 113.26-117.74 mm and 89.63-102.76 g g then female: 114.36 mm and 106.51 g), Pasuruan (male: 87.66-94.43 mm and 39.68-49.90 g then female: 101.94-110.89 mm and 66.98-82.89 g), and Rembang (male: 120.30-126.69 mm and 93.53-118.43 g then female: 125.30-132.13 mm and 134.42-157.47 g); sex ratio (male: female) in Lamongan (1.4: 1), Tuban (1: 1.5), Pasuruan (2.8: 1), and Rembang (1: 1.46); and also gonad maturity level in Lamongan (dominant male at level III was 30.29%, female at level II and III was 30.40%), Tuban (dominant male at level II was 41.93%, female at level III was 33.33%), Pasuruan (dominant male at level III was 25.79%, female at level III was 48.10%), and Rembang (dominant male at level II was 32.35%, female at level II was 33.33%). These results indicate that the total of Portunus pelagicus which was being caught had fulfilled the standards rules by No.1/PERMEN-KP/2015. However, it requires continuous direct monitoring and counseling to maintain the stock of blue swimmer crab resources. Keywords: Blue swimmer crab (Portunus pelagicus), gonad maturity level, sex ratio, wide and weight.